An amyotrophic lateral sclerosis-like syndrome revealing an amyloid polyneuropathy associated with a novel transthyretin mutation. (5th August 2013) - Lozeron, Pierre; Lacroix, Catherine; Theaudin, Marie; Richer, Anne; Gugenheim, Michel; Adams, David; Misrahi, Micheline
Abstract: Objective : Familial amyloid polyneuropathy (FAP) is typically a predominantly sensory and autonomic neuropathy with progressive and late motor involvement leading to death within 10 years. Recently, prognosis was transformed with liver transplantation. Methods : We report an atypical sporadic pure motor and bulbar neuropathy initially mistaken for amyotrophic lateral sclerosis (ALS) in a 50-year-old Malian man. Results : The diagnostic procedure of this clinical purely motor and bulbar neuropathy disclosed amyloid deposits on nerve biopsy which led to the identification of a new Val93Met mutation of transthyretin. This case was also remarkable by its slow progression. Conclusions : This report confirms the motor phenotype of TTR-FAP. That should be considered in the differential diagnosis of motor neuron diseases in order to start accurate therapy.